Measuring Regional Innovative Capability - Tomi Tura; Vesa Harmaakorpi (European Regional Science Association (ERSA), 2005)
Regional innovation environment has experienced remarkable changes in the recent decades. Innovativeness at regional level is seen as a consequence of networked co-operation in a regional innovation system, which sets demands for new kinds of regional innovation policy applications. The current article presents network-facilitating innovation policy (NFIP) as a policy tool for promoting regional innovative capability. The new policies are crying out for new means for evaluating changes in regional innovation systems. There have been some interesting efforts to develop adequate measures for regional innovativeness. However, there are several problems with the existing measures. There seems to be a lack of clear distinction between innovation performance and innovative capability, and a corresponding neglect of the latter. Moreover, it is argued that the existing measures undermine the processual nature of innovativeness as well as the importance of non-technological innovations. The present article tries to overcome some of these problems in the context of network-facilitating innovation policy. It outlines the framework of network-based innovative capability (NBIC) measure at a regional level. The article also presents the first experiences of applying NBIC measure in the Lahti region in Finland.
Keywords: 330